14C GEOCHRONOLOGY AND RADIOCARBON RESERVOIR EFFECT OF REVIEWED LAKES STUDY IN CHINA. Issue 4 (3rd August 2022) - Zhou, Weijian; Chui, Yuda; Yang, Ling; Cheng, Peng; Chen, Ning; Ming, Guodong; Hu, Yan; Li, Wenli; Lu, Xuefeng
ABSTRACT: Lacustrine sediments are important archives for paleoclimate research, but there are evident carbon reservoir effects. Radiocarbon ( 14 C) ages of lake sediments must be corrected for these effects before applying them to paleoclimate research. The authors review the lacustrine research from the last 20 years from different climatic regions in China, and systematically investigate the 14 C age and correction methods used in the studies of 81 lakes. It is found that the climate-vegetation cover and distribution of carbonate around lakes are dominant factor controlling radiocarbon reservoir effects. In eastern China, the average 14 C reservoir age is about 500 14 C years and is associated with relatively dense vegetation. However, in northwest China and Qinghai-Tibet Plateau, widespread carbonate bedrock may markedly increase the radiocarbon reservoir age which frequently is about 1500 and 2500 14 C years. A piecewise linear regression model provides more reliable 14 C reservoir age correction that accounts for sedimentary facies and sedimentation rate changes. It is worth mentioning that when analyzing 14 C ages deviated greatly from time sequence, the age anomalies may indicate important effects relevant to the study of climate and environmental changes.